PEMBUATAN ALAT UKUR PENELITIAN DIFRAKSI CAHAYA BERBASIS VISION ASSISTANT DAN LABVIEW - Novin Syahputra; Sunaryo Sunaryo; Prawito Prawito; Sastra K. Wijaya (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
It has created a measuring instrument which can measure light intensity distribution pattern. By exploiting phenomenon the nature of light, the author would like to know the value of wave length and the intensity distribution of the diffraction pattern on laser light that passes through a diffraction grating so it can be appropriate to reference theory. The source of light use red of monochromatic, polychromatic light which produce RGB color and mercury lamp. Grating diffraction and source of light are moved by DC motor with go forward and go back moving, which next by rotary encoder change distance become counter in partition. The all of these moving are manage by LabVIEW National Instrument and processing of image is executed of Vision Assistant program. The result of research is red monochromatic with width diffraction grating 300 lines/mm, is produced wave length of light (640 - 676) nm. For blue color with width diffraction grating 600 lines/mm, is produced wave length of light (454 - 475) nm. For green color with width diffraction grating 600 lines/mm, is produced wave length of light (524 - 547) nm. For red color with width diffraction grating 600 lines/mm, is produced wave length (654 - 697) nm. The greater order of diffraction then the less level of intensity was resulted. Keywords : diffraction of light, DC motor, LabVIEW, wave length.